A long-term clinical trial on the efficacy and safety profile of doxofylline in Asthma: The LESDA study. (February 2020) - Calzetta, Luigino; Matera, Maria Gabriella; Goldstein, Marc F.; Fairweather, William R.; Howard, William W.; Cazzola, Mario; Rogliani, Paola
Abstract: Doxofylline, an oral methylxanthine with bronchodilator and anti-inflammatory activities, offers a promising alternative to theophylline due to its superior efficacy/safety profile. No long-term studies on the efficacy and safety of doxofylline are currently available in asthma. The aim of the Long-term clinical trial on the Efficacy and Safety profile of Doxofylline in Asthma (LESDA) study was to investigate the safety and efficacy profile of doxofylline administered for one year in asthmatic patients. LESDA was a multicenter, open-label, Phase III, clinical trial in which adult asthmatic patients received the same treatment (oral doxofylline 400 mg t.i.d.) for one year. Efficacy was assessed through periodic pulmonary function tests and by having the subjects keep monthly records of asthma events rates and use of salbutamol as rescue medication. The rate of adverse events (AEs) was recorded during the study. Three-hundred nine patients were screened and allocated in the study. Doxofylline significantly improved the change from baseline in forced expiratory volume in 1 s (FEV1 ) (+16.90 ± 1.81%, P < 0.001 vs. baseline). Doxofylline also significantly improved the rate of asthma events (events/day: -0.57 ± 0.18, P < 0.05 vs. baseline) and the use of salbutamol as rescue medication (puffs/day: -1.48 ± 0.25, P < 0.01 vs. baseline). The most common AEs were nausea (14.56%), headache (14.24%), insomnia (10.68%), and dyspepsia (10.03%). There were neither serious AEs nor deaths during or shortly after the study. Concluding, doxofylline is effective and well tolerated when administered chronically in asthmatic patients.